Pioglitazone Ameliorates Renal Ischemia-Reperfusion Injury via Inhibition of NF-κB Activation and Inflammation in Rats - Zou, Gaode; Zhou, Zhiyu; Xi, Xiaoqing; Huang, Ruizhen; Hu, Honglin (Frontiers in Physiology, 2021)
Renal ischemia-reperfusion injury (IRI) is considered as a major cause of acute kidney injury. In this study, we investigated the role of the NF-κB signaling pathway and inflammation in the amelioration of renal IRI using pioglitazone. Sprague-Dawley rats were subjected to bilateral renal artery clamping for 45 min followed by perfusion restoration for establishing a simulated renal IRI model. At 24 h post-operatively, we assessed the serum levels of creatinine and urea nitrogen, expression levels of peroxisome proliferator-activated receptor gamma (PPAR-γ) and NF-κB-related (p-IKK-β and IκB-α) proteins, and mRNA expression levels of the inflammatory cytokines, including TNF-α and MCP-1, in the renal tissue of various study groups. The histopathological evaluation of renal tissue was also conducted. In rat renal tissue, pioglitazone treatment decreased the serum levels of post-renal IRI creatinine and urea nitrogen, as well as necrosis. Furthermore, it elevated the expression of PPAR-γ protein and decreased the expression of NF-κB-related proteins. Pioglitazone also decreased the mRNA expression of TNF-α and MCP-1 in the renal tissue. Thus, pioglitazone ameliorates renal IRI by inhibiting the NF-κB signaling pathway and inflammatory response in rats.